Wanpaku sandwich / Wan Anisha Wan Mohammad and Rafizah Kechil - Wan Mohammad, Wan Anisha; Kechil, Rafizah (Unit Penerbitan Dan Publisiti JSKM, 2024)
Steps to make wanpaku sandwich 1- place 3 slices of bread on the food wrapping spread butter on the bread. 2- put any fillings on the first bread. Put some sauce on it. 3- put another slice of bread on top of it and put vegetables on the second slice of bread. Cover the sandwich with third slice of bread.